Eksplorasi Sejarah Sungai Bengawan Solo sebagai Salah Satu Materi Pembelajaran Sejarah Lokal di Sekolah Menengah Atas - Anang Haris Himawan; Susanto Susanto; Hieronymus Purwanta (Department of History, Faculty of Humanities, Diponegoro University, 2021)
Bengawan Solo River has been flown since prehistoric times. It had its headwaters at the downstream of the ancient Mount Merapi in southern Java and downstream into the South Coast, and then moved to its estuary on the North Coast. The Bengawan Solo River has potential role in the past as an economic medium, for trading and transportation route which had served in all the regions of Java. This vital function however, is not widely exposed. Exploration of river history of the Bengawan Solo has not been fully revealed and still under further research. The method used to reveal the river’s function is used historiographical method by emphasizing several literatures sourced from textbooks, scientific journals, and others. Through this study, it is known that the Bengawan Solo River had served vital functions as a basis for economic activity, trade, and transportation route which was from the Majapahit Kingdom to the 19th century. The vitality of the river needs to be used as one of the historical learning materials at the high school to rise awareness about local history potential, especially in Surakarta. Therefore, the qualitative method indicators from G. Moedjanto and Soejatmoko is used to analylze local history consciousness. To examine the data validity, triangulation and data analysis techniques were used, in the form of the interactive model from Miles dan Hubermen. According to the result, it highlights two important aspects of local history learning materials in schools, namely geomorphological development and fulfillment of economic functions. This learning is important to arise historical consxiousness in the context of locality among all students.